The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1590/s1984-70332011000200002
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of genetic gains from selection in Arabica coffee progenies

Abstract: -Gains from selection for yield were estimated in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 10 publications
1
13
0
2
Order By: Relevance
“…The group with the highest values comprised the genotypes P2, Z39, A1, Peneirão, Cheique, Bamburral, Bicudo, Tardio C, Z37, Z21, Z38, Z29, Ouro Negro and L80 for PSBD; genotype 18 had the highest value for NIPS (Table 1). Higher values for NPTB and PSBD are desirable, as they exhibit high correlation with productivity in future harvests (Bustamante et al, 2004;Contarato et al, 2010), and productivity is the main objective and selection criteria in coffee cultivation (Oliveira et al, 2011;Rodrigues et al, 2014). No significant differences were observed among the analysed genotypes in SSH, SSBD, or NISS (Table 2).…”
Section: Growth and Development Initialmentioning
confidence: 96%
“…The group with the highest values comprised the genotypes P2, Z39, A1, Peneirão, Cheique, Bamburral, Bicudo, Tardio C, Z37, Z21, Z38, Z29, Ouro Negro and L80 for PSBD; genotype 18 had the highest value for NIPS (Table 1). Higher values for NPTB and PSBD are desirable, as they exhibit high correlation with productivity in future harvests (Bustamante et al, 2004;Contarato et al, 2010), and productivity is the main objective and selection criteria in coffee cultivation (Oliveira et al, 2011;Rodrigues et al, 2014). No significant differences were observed among the analysed genotypes in SSH, SSBD, or NISS (Table 2).…”
Section: Growth and Development Initialmentioning
confidence: 96%
“…Thus, clustering techniques and principal component analyses can help guide the selection of genotypes that are better suited to a growing region. In genetic breeding, studies on gain prediction by selection strategy provide a more efficient orientation to breeding programs and the choices of alternatives and more effective techniques based on scientific evidence (Oliveira et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics such as the number of reproductive nodes, number of leaves, leaf area, specific leaf area, chlorophyll content and area, and mass ratios have been previously used in biometric studies of diversity among genotypes of Arabica coffee and showed high genetic variability in some of these traits (Rodrigues et al, 2014a). Oliveira et al (2011) also observed a considerable genetic variability among genotypes of Arabica coffee, which was enough to allow selection gains based on crop yield, both using the first high harvest only and the mean of the first four harvests.…”
Section: Discussionmentioning
confidence: 92%